1976
DOI: 10.1128/jvi.19.2.457-466.1976
|View full text |Cite
|
Sign up to set email alerts
|

Association of the polioviral RNA polymerase complex with phospholipid membranes

Abstract: Polioviral RNA polymerase complex, which consists of enzyme, template, and nascent RNA, is membrane bound in vivo. The solubilized RNA polymerase complex associated spontaneously in vitro with phospholipid bilayer membranes (liposomes) of defined composition. The degree of association at 37°C was greater for those membranes that were more fluid, suggesting that the binding involves the interaction of the RNA polymerase complex with the hydrocarbon chains in the interior of the lipid bilayer. The polymerase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Previous data suggested that protein 2C is involved in RNA synthesis. The high degree of amino acid sequence conservation of protein 2C among picornaviruses (1,10,23) argues for its importance, and the demonstration that 2C is associated with the membrane-bound viral replication complexes in poliovirus-infected cells (5,6,33) suggests that it is inherent in the replication process. This perspective is further supported by the observation that several guanidineresistant and guanidine-dependent poliovirus mutants map to within the region that encodes protein 2C (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data suggested that protein 2C is involved in RNA synthesis. The high degree of amino acid sequence conservation of protein 2C among picornaviruses (1,10,23) argues for its importance, and the demonstration that 2C is associated with the membrane-bound viral replication complexes in poliovirus-infected cells (5,6,33) suggests that it is inherent in the replication process. This perspective is further supported by the observation that several guanidineresistant and guanidine-dependent poliovirus mutants map to within the region that encodes protein 2C (15,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…" All single and mixed infections were carried out at 39.5°C for 4 h with a multiplicity of infection of 5 for each virus 6. Titers of the viruses harvested from single or mixed infections containing 106 HeLa cells each in 2 ml of minimal essential medium.…”
mentioning
confidence: 99%
“…In retroviruses, this is made possible by a physical linkage of two RNA templates in heterozygotes, thus facilitating template switching (18). In most RNA viruses, RNA synthesis occurs in membraneassociated compartments, thus allowing a local concentration of RNA molecules (11,16,23,62). It also has been proposed that the complementary sequence in the secondary structure of RNA could allow two different RNA molecules to form a heteroduplex (14,56,87).…”
Section: Physical Requirements Of Template Switchingmentioning
confidence: 99%
“…panels). All three proteins 2B, 2C and 2BC seem to interact with membranes in mammalian cells (Butterworth et al, 1976;Bienz et al, 1983;Tershak, 1984). To test this possibility in yeast cells, we employed standard differential centrifugation techniques to fractionate yeast lysates from spheroplasts (Bankaitis et al, 1989).…”
Section: Morphological Alterations Of Yeast Cells That Synthesize Polmentioning
confidence: 99%
“…With regard to the generation of these membranous structures and the viral proteins involved in this process, it was found that apart from the viral RNA polymerase, 3DP°1, other viral non-structural proteins were tightly associated with the poliovirus replication complexes (Girard and Baltimore, 1967;Butterworth et al, 1976;Bienz et al, 1983;Tershak, 1984). Of interest in this regard was the association of 2BC and 2C not only with the membrane vesicles, but also with the viral nucleic acids (Butterworth et al, 1976;Bienz et al, 1983;Tershak, 1984). Initial studies localized several poliovirus proteins in these membranous vesicles and suggested that the precursor 2BC could play an important part in the generation of the vesicles (Bienz et al, 1983).…”
Section: Introductionmentioning
confidence: 99%